Empowering rural adolescents in emergency response through first Aid App and indigenous-language short films - Ekaprasetia, Feri; Madyaning Nastiti, Eky; Darotin, Rida; Wahyu Wulansari, Yunita; Wirasakti, Guruh; Manuel Correia Ximenes, Joao (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2025)
First aid competence among adolescents is a crucial component of community-based disaster risk reduction, particularly in rural areas with limited access to emergency healthcare services. This study aims to evaluate the effectiveness of the First Aid Guidelines (FAG) mobile application and an indigenous-language short films in improving first aid knowledge, attitudes, and skills among junior high school students in a rural Indonesian setting. A quasi-experimental study without a control group involved 120 students who were selected through simple random sampling. Data were collected using validated questionnaires and simulation-based assessments. Statistical analysis employed the Wilcoxon and the Mann-Whitney U tests. Both the FAG application and the short film significantly improved students' first aid knowledge (p=0.001), with no significant difference in effectiveness between them (p=0.955). The FAG application significantly enhanced students' attitudes (p=0.001), while the short film did not (p=0.207). Conversely, the short film significantly improved practical first aid skills (p=0.001), but the application did not (p = 0.115). There were no statistically significant differences found between the two media in terms of attitude (p=0.955) and skill improvement (p=1.000). The use of both the FAG application and a culturally adapted short film was effective in improving rural adolescents' first aid knowledge. The FAG application was more impactful in shaping positive attitudes, but thee short film demonstrated greater efficacy in improving practical skills. The use of application-based educational technology and short films in school health curricula is recommended to enhance first aid skills in adolescents.